PENGARUH SUKU BUNGA, KURS RUPIAH DAN INFLASI TERHADAP HARGA SAHAM SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2014 - 2018 - Helvoni Mahrina (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2022)
This study aims to analyze whether interest rates, rupiah exchange rates and inflation affect stock prices in banking sub-sector companies on the Indonesia Stock Exchange in 2014 - 2018. The study was conducted on 27 banking sub-sector companies listed on the Indonesia Indonesia Stock Exchange. The data analysis method uses multiple linear regression, determination test and hypothesis testingThe results showed that the X1 variable (interest rate) obtained a significance value of 0.020 <0.05, meaning that X1 (interest rate) had an effect on stock prices (Y) in banking sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Variable X2 (the rupiah exchange rate) obtained a significance value of 0.041 < 0.05. Because the significance value is less than 0.05, it means that X2 (the rupiah exchange rate) has no effect on the stock price (Y) of the banking sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Variable X3 (inflation) obtained a significance value of 0.195> 0.05. Because the significance value is greater than 0.05, it means that X3 (inflation) has no effect on stock prices (Y) in banking sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Simultaneous hypothesis testing showed a significance value of 0.020 <0.05. This means that together X1 (interest rate), X2 (rupiah exchange rate) and X3 (inflation) affect stock prices (Y)